Teams' reponses to changed incentives: Evidence from Rugby's Six Nations Championship - Vincent Hogan; Patrick Massey (University College Dublin, UCD School of Economics, 2015)
The paper analyses teams' responses to rule changes designed to encourage more entertaining play in Rugby Union's Six Nations Championship. We use a data set of all scores in the competition since 1883 to analyse the impact of rule changes on teams' strategic decisions. We find that increasing the points for a try leads to more tries per match. We also find evidence that teams may be prepared to concede penalties, which are worth fewer points in order to prevent more costly tries. The switch to a winner takes all format in 1994 also led to more tries being scored. Unlike most other major rugby competitions, the Six Nations does not award bonus league points for scoring a certain number of tries and we consider whether this would increase try scoring. Our results may have practical applications given ongoing concerns about a decline in try scoring in the Six Nations.
Keywords: 330